Line parameters of the P-branch of (30012) ← (00001) 12C16O2 band measured by comb-assisted, Pound-Drever-Hall locked cavity ring-down spectrometer. (April 2021) - Guo, Ruimin; Teng, Junheng; Dong, Hewei; Zhang, Tiqiang; Li, Dong; Wang, Defa
Highlights: The P-branch of the (30012) ← (00001) band of 12 C 16 O2 has been studied with a comb-assisted, Pound-Drever-Hall locked cavity ring-down spectrometer. Line parameters including transition frequency, line intensity, pressure broadening and shifting coefficients are simultaneously retrieved for lines with rotational quantum number extending to -72. The uncertainties for the measured spectroscopic parameters are lower than those from HITRAN 2016 and CDSD-296 databases. The measured transition frequencies agree well those from HITRAN 2016 and CDSD-296 for rotational quantum number m from -32 to -2. Comparatively, the measured transition frequencies show a clear tendency of being smaller for m below -32. Abstract: This article presents an accurate measurement of line parameters for the P-branch of (30012)←(00001) 12 C 16 O2 band with rotational quantum number extending to -72. The spectrometer has a temperature stability of below 0.5 mK at 296 K and a cavity leakage of 0.068 mTorr/hour. An optical frequency comb is employed to measure the absolute transition frequencies. The measured data are processed using multi-spectrum fitting method with different line-shape models to retrieve line positions, intensities, and other line-shape parameters. The correlation between Dicke narrowing and speed-dependent broadening is studied. The measured parameters are compared to a series of spectroscopic databases and previously published results.